Decarbonization Options in the Russian Energy Sector: a Comparative Study on Their Economic Efficiency - Keiko, Alexander; Veselov, Fedor; Solyanik, Andrey (International Journal of Energy Economics and Policy, 2022)
The study is focused on the comparison of how costly different decarbonization options in Russia are, in terms of their total expenses per a unit of CO2 avoided. We have constructed two marginal abatement cost curves reflecting different decarbonization policies in the Russian energy sector – basic and intensive scenarios. Doing that, we tried to adequately represent economic, regulation and climatic features of Russia (for instance, relatively low capital cost for most of the technologies, typical wind and solar conditions, regulation policy on natural gas cost, etc.). We found that non-carbon transport and energy savings in the demand side seem to be the most affordable decarbonization options in our country while solar heat, nuclear cogeneration and hydrogen as a carrier are uncompetitive in both scenarios observed.